2008
DOI: 10.2174/1874140100802010012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capping Agent Concentration on Photophysical Properties of Zinc Sulfide Nanocrystals

Abstract: Zinc Sulfide (ZnS) nanoparticles with varying concentration of capping agent were prepared using chemical technique. These particles were characterized using scanning electron microscope (SEM), atomic force microscope (AFM) and x-ray diffraction (XRD). It is observed that particle size decreases with increasing capping agent concentration. Optical absorption studies show that the absorption edge shifts towards blue region as the capping agent concentration is increased indicating that effective band gap energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Subsequently, the emitted photon has comparatively lower energy giving photoluminescence peak at higher wavelength. Chen et al [41] has also reported PL peak of ZnS in this range, while Tamrakar et al [42] obtained the PL peak at 460 nm for uncapped ZnS nanoparticles, which then shifted up to 370 nm as capping concentration increased.…”
Section: Optical Propertiesmentioning
confidence: 92%
“…Subsequently, the emitted photon has comparatively lower energy giving photoluminescence peak at higher wavelength. Chen et al [41] has also reported PL peak of ZnS in this range, while Tamrakar et al [42] obtained the PL peak at 460 nm for uncapped ZnS nanoparticles, which then shifted up to 370 nm as capping concentration increased.…”
Section: Optical Propertiesmentioning
confidence: 92%
“…There are several methods to synthesize ZnS nanoparticles with various Mn 2+ concentrations such as sol-gel, chemical vapour deposition, and chemical co-precipitation method hydrothermal method [49][50][51][52]. So among the different synthesis processes, chemical co-precipitation method is used because of its manifold advantages like simple, easy handling, economical and capability for large scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Optical excitation of electrons across the band gap is strongly allowed, producing an abrupt increase in absorption at the wavelength corresponding to the band gap energy. This feature in the optical absorption spectrum is known as the optical absorption edge [21]. It may be mentioned that the optical absorption spectra recorded in the visible and near infrared (NIR) regions are related to the electronic transitions, which are useful in understanding the electronic band structure of the deposited films [22].…”
Section: Optical Propertiesmentioning
confidence: 99%